2016
DOI: 10.1007/978-3-319-30137-2_11
|View full text |Cite
|
Sign up to set email alerts
|

Design Optimization of Silicon-on-Insulator Slot-Waveguides for Electro-optical Modulators and Biosensors

Abstract: An approach for design optimization of the geometrical parameters of silicon-on-insulator slot-waveguides for electro-optical modulators and biosensors is presented. Theoretical investigations of field confinement factors and effective nonlinear areas for different slot-waveguide structures are critically analyzed and thoroughly calculated. With our simulation results we explain the high efficiency of electro-optical modulators and the enhanced sensitivity of biosensors compared to strip-waveguides. The influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The most important component of all integrated photonic biosensors is the silicon waveguide. During the last decade, many effort has been undertaken to improve waveguide geometries for optical sensing by simulation studies [38,39,40]. In principle, there are three types of widely used waveguides, namely strip waveguide, rib waveguide and slot waveguide, as illustrated in Figure 2.…”
Section: Photonic Devices and Sensing Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important component of all integrated photonic biosensors is the silicon waveguide. During the last decade, many effort has been undertaken to improve waveguide geometries for optical sensing by simulation studies [38,39,40]. In principle, there are three types of widely used waveguides, namely strip waveguide, rib waveguide and slot waveguide, as illustrated in Figure 2.…”
Section: Photonic Devices and Sensing Mechanismsmentioning
confidence: 99%
“…From Figure 3 it is apparent that the highest optical field confinement in the cladding is provided by the slot waveguide structure. Simulation studies have revealed that SOI slot waveguides achieve an optical field confinement of 0.7, i.e., 70% of the guided light is confined in the cladding and not in the silicon core [39,40,41]. In contrast, strip waveguides achieve an optical field confinement factor of 0.2.…”
Section: Photonic Devices and Sensing Mechanismsmentioning
confidence: 99%
“…To describe the interaction of light with the surrounding material, the field confinement factor Γ is used as a figure of merit to characterize devices like slot-waveguides and their ability to confine an optical mode within a certain region [19]. The field confinement factor is defined as the ratio of the time averaged energy flow through the area of interest A int to the time averaged energy flow through the total area A tot [20]…”
Section: Field Confinement Factormentioning
confidence: 99%
“…SEM image (left) of slot waveguides with different slot widths fabricated using 248 nm lithography. FIB image (right) of a slot waveguide cross section [13].…”
Section: Silicon-on-insulator Slot Waveguide Theorymentioning
confidence: 99%